Learning to Read and Spell: How Children Acquire Word Orthographic Knowledge. (14th July 2015) - Bosse, Marie‐Line
Abstract: In this article, I review knowledge about the cognitive abilities involved in a crucial stage of developing reading and spelling expertise: acquiring knowledge of the orthographic structure of words. Specifically, I focus on three abilities that seem fundamental for this acquisition: (a) decoding ability—because most word orthographic knowledge is acquired implicitly during reading, the ability to deduce the pronunciation of a word from its written form is essential; (b) the ability to process simultaneously all the letters of the word that is read, an ability that is also involved in implicit acquisition and supported by both theoretical and empirical data; and (c) the ability of handwriting to enhance word orthographic acquisition. I conclude with practical consequences for teaching literacy and detecting reading and spelling difficulties early.